Night heart rate variability during overtraining in male endurance athletes - Bosquet, L.; Papelier, Y.; Leger, L.; Legros, P. (The Journal of Sports Medicine and Physical Fitness, 2003)
Aim: The purpose of the study was to examine whether an unaccustomed increase in training volume would result in characteristics changes in heart rate variability (HRV), in order to determine if this marker can be used to diagnose overtraining. Methods: Nine experienced endurance athletes increased their usual amount of training by 100% within 4 weeks. Night ECG was recorded before (baseline) and after (OVER) this period of overload, and after 2 weeks of recovery (REC). Results: We diagnosed overtraining in 6 subjects using both physiological and psychological criteria. No difference was noted in heart rate for night periods (56±12, 55±10 and 53±15 bpm, respectively; p>0.05). We found no significant changes of LF/HF (1.10±0.92, 0.96±0.57 and 0.59±0.43, respectively; p>0.05) or HF expressed in normalized units (54.81±20.12, 53.81±11.35 and 66.15±15.12%, respectively; p>0.05). Conclusion: In the conditions of the present study, HRV during sleep does not seem to be a valid marker of overtraining in male endurance athletes. Before concluding to the uselessness of this tool in the monitoring of the syndrome, longitudinal studies with elite or sub-elite athletes are needed to determine if spontaneously developed overtraining results in the same response.